Scenographic museography and digital technology as a combination of exhibition possibilities. James Turrell's chromatic installations as an example of immersive exhibitions (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This article explores how, based on the curatorial narratives of museum curators, the increasingly frequent use of scenography has been imposed as a way of bringing exhibition events closer to a larger number of visitors. This approach, through the disciplinary hybridization offered by scenography as an approach to the total work of art, makes them more attractive and stimulating. Thus, it configures a new category of (scenographic) museology. In the context of the current mass culture that equates tourism with visits to mega-exhibitions, the role that digital technologies play in this context, in terms of increasing spatial possibilities, is clarified. In this regard, the case of the recently much-publicized immersive exhibitions is analyzed as an extreme case of meta-artistic exhibitions. In contrast, reference is made to an essential scenographic use of color, by James Turrell, so that it is precisely this ultimate contrast offered by this example, and after having delved into the scenographic potential for the development of new expository narratives today, which provides us with consistent final conclusions.
Keywords: Scenographic museology; digital technology; immersive installations; James Turrell